Female-Biased Expression of R-spondin 1 in Chicken Embryonic Gonads Is Estrogen-Dependent - Mingde Zheng; Xikui Liu; Yu Meng; Xiao Lin; Jiahui Li; Jianguo Zhu; Minmeng Zhao; Long Liu; Tuoyu Geng; Daoqing Gong; Jun Zhang (Animals, 2023)
The mechanism of sex determination in chickens, especially the molecular mechanism of female ovarian development, has not yet been fully elucidated. Previous studies have shown that RSPO1, which is associated with ovarian development in mammals, might have a conserved role in chickens. In this study, we systematically investigated the spatiotemporal expression pattern of RSPO1 in various tissues, especially gonads, of male and female chicken embryos using qPCR and Western blotting, and we explored its correlation with the expression of key genes in the estrogen pathway using drug treatment or gene overexpression in vivo and in vitro. Our results reveal that RSPO1 was widely expressed in all examined tissues of chicken embryos, showing a female bias in gonadal tissues at both the mRNA and protein levels. Surprisingly, RSPO1 was not differentially expressed between male and female gonadal cells with fadrozole-induced estrogen pathway blockades, and furthermore, estradiol-induced estrogen stimulation altered the expression of RSPO1. In addition, overexpression of RSPO1 in gonadal cells induced the mRNA expression of its downstream target genes, Wnt family member 4 (WNT4) and Catenin beta 1 (CTNNB1), and that of estrogen receptor α (ERα), an estrogen pathway gene. In summary, this study provided new evidence for elucidating the role of RSPO1 in ovarian development in poultry.